Cyclic Peptides as Protein Kinase Modulators and Their Involvement in the Treatment of Diverse Human Diseases - Lorena Martínez-Alcantar; Laura Hernández-Padilla; Alma Laura Díaz-Pérez; Lizbeth Guadalupe Villalón-Magallán; Mayra Xóchitl Durán-Maldonado; César Díaz-Pérez; Marlene E. Campos-Morales; Citlali Figueroa-Guzmán; Jesús Campos-García (Kinases and Phosphatases)
Protein kinases (PKs) are an important and very popular family of enzymes that play a vital role in regulating cellular processes via the phosphorylation of targets. Nevertheless, modifications in the expression due to mutations or their dysregulation can lead to diseases, including autoimmune disorders, cardiovascular problems, diabetes, neurological diseases, and cancers. Cyclic ultra-short peptides are amazing structures with unique properties. The cyclicity of cyclic peptides (CPs) can mimic the interactions between PKs and natural substrates, influencing the enzyme activity essential in health and disease physiology. Our review summarized that interference in the signal transduction mechanism of the PKs by CPs implies the inhibition of substrate phosphorylation at the level of the active site, similar to anti-neoplastic drugs. The remarkable capacity of CPs to interact with targets positions them as promising candidates for developing protein kinase inhibitors in treating diseases. This review offers new insights for CPs in molecular mechanisms, cytotoxicity, target selectivity, and the possibility of designing more effective and safe therapeutic agents.